2018
DOI: 10.1021/acs.chemmater.7b04962
|View full text |Cite
|
Sign up to set email alerts
|

Substituting Copper with Silver in the BiMOCh Layered Compounds (M = Cu or Ag; Ch = S, Se, or Te): Crystal, Electronic Structure, and Optoelectronic Properties

Abstract: The synthesis of BiAgOCh (Ch = S or Se) compounds has been successfully achieved via the ion exchange of copper with silver in aqueous solutions, starting from the copper parent phase. Optical and electrical measurements of BiAgOCh powders confirm an increase in both the bandgap and the electrical resistivity, as compared to those of the copper compounds. The structure of the BiAgOS phase has been clearly examined. X-ray diffraction synchrotron measurements coupled with advanced high-resolution transmission el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 41 publications
3
35
0
Order By: Relevance
“…This method above with the simulation package Phono3py code [23] has been successfully applied to predicting the thermal conductivities of many other materials, such as ZrNiPb [25] , BiTeBr [26] , and TaCoSn [27] et al respectively, which are close to the experimentally measured values [8] . These smallish differences are mainly due to the fact that GGA often overestimates the lattice constants of solids [28] .…”
Section: Computational Detailssupporting
confidence: 53%
See 1 more Smart Citation
“…This method above with the simulation package Phono3py code [23] has been successfully applied to predicting the thermal conductivities of many other materials, such as ZrNiPb [25] , BiTeBr [26] , and TaCoSn [27] et al respectively, which are close to the experimentally measured values [8] . These smallish differences are mainly due to the fact that GGA often overestimates the lattice constants of solids [28] .…”
Section: Computational Detailssupporting
confidence: 53%
“…Recently, BiCuOSe oxyselenides have acquired ever-increasing attention as very promising thermoelectric materials due to their high value of ZT (1.5 at 900 K) [7][8][9][10][11][12] . The outstanding TE properties could be mainly ascribed to their intrinsically low thermal conductivity of BiCuOSe and its alloys [13][14][15][16][17][18] .…”
Section: Materials Advances Accepted Manuscriptmentioning
confidence: 99%
“…The Bi 2 S 3 / AgBiS 2 NHSs show a nearly 17 times higher photocurrent gain value than that of the pure Bi 2 S 3 . Photocurrent gain for pure AgBiS 2 NRs is superior to that of a BiAgOS (∼50) compound possibly due to one-dimensional morphology …”
Section: Resultsmentioning
confidence: 98%
“…In this regard, the CE process opens up a new window to synthesize ternary materials staring from a binary parent material. In earlier studies, it was reported that bismuth silver oxysulfide (BiAgOS) can be synthesized from the parent copper compound (BiCuOS), employing the cation exchange of Cu + by Ag + ion. , The favorable semiconducting properties of BiAgOS having a bandgap of ∼1.5 eV give rise to interesting photoconversion applications. The compound BiAgS 2 is isoelectronic to BiAgOS, and its comparable bandgap value may be attractive to design a photodetector.…”
Section: Introductionmentioning
confidence: 99%
“…This photoconductivity effect represents a substantial increase compared to that of BiCuOS measured separately, previously reported, for which I ph /I dark = 0.5. [41] The junction is therefore strongly photosensitive and could be used as a photodetection device for instance. The most common inorganic phases reported as p-type absorber layers in photodiode or photovoltaic pn junctions are Si, GaAs, CdTe, InP, CuInSe 2 , Zn 3 P 2 , CIGS (CuIn x Ga y Se), CZTS (Cu 2 ZnSnS 4 ), WSe 2 .…”
Section: Thin Film Depositionmentioning
confidence: 99%